Partial Discharge Phase Distribution of Palm Oil as Insulating Liquid - Abdul Rajab; Umar K. Umar K.; D. Hamdani D. Hamdani; Aminuddin S. Aminuddin S.; Suwarno Suwarno; Y. Abe Y. Abe; M. Tsuchie M. Tsuchie; M. Kozako M. Kozako; S. Ohtsuka S. Ohtsuka; M. Hikita M. Hikita (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Due to the low biodegradability level of mineral oil and its susceptibility to the fire, palm oil was proposed as alternative insulating liquid. This paper discusses partial discharge (PD) in palm oil under sinusoidal voltages and the comparison with mineral oil. PD was generated using a needle-plane electrode configuration which is enable enhancing electric field at the needle tip. PD pulses were detected using RC detector and they were measured using a Computer-based partial discharge measurement system. The results showed that PD activities in both oils are similar. The PD was initiated at the negative polarity of applied voltage. The discharges took place in both polarity’s of applied voltage with PD number was higher at negative one. Several discharges phenomena showed the presence of space charge which changed electric field and governed PD activities besides the main field introduced by voltage application.